Tattered trust: is there hope for your denomination? - Schaller, Lyle E. (Ministry for the third millenium, 1996)
All Protestant denominations face difficult times ahead. Some are merely surviving financial crisis. Many have no compelling direction regarding missions and evangelism. Most are in denial about the outcome. In Tattered Trust, Lyle E. Schaller argues that there is hope for denominations. With special focus on The Episcopal Church. The evangelical Lutheran Church, The Presbyterian Church (U.S.A.), The Southern Baptist Convention, and The United Methodist Church, he offers seven scenarios that local church and denominational officials can pursue as each church leader confronts the opportunity of whether to be a victim or a reformer.